Benchmarking present and future performances of coastal and island settlements with the Sustainable Development of Energy, Water and Environment Systems Index - Şiir Kilkiş (Journal of Sustainable Development of Energy, Water and Environment Systems, 2024)

(untitled)
The renewable energy transition and integrated approaches are ever more important for cities in a rapidly changing climate. This research work focuses on benchmarking 11 coastal and coastal island cities based on the Sustainable Development of Energy, Water and Environment Systems Index. The coastal and coastal island cities are located in the Mediterranean Sea Basin, including on the islands of Mallorca, Sardinia, and Sicily. The method involves benchmarking present performance levels and possible future performances considering a numerical 100% renewable energy scenario in which energy usage is decoupled from carbon dioxide emissions for complete elimination of the latter. The results of present levels of benchmarked performance indicate that the top cities are Messina, Siracusa, and Palermo. Shortcomings limit all of the analysed coastal and coastal island cities from reaching an upper quartile that represents the pioneering cities among a total of 132 cities that are benchmarked with the composite indicator to date. All else being equal, the exemplary scenario enables an upward shift in performance, with 6 of the cities reaching the upper quartile of the pioneering cities. Additional analyses are conducted to estimate the local job opportunities that can be established through the realization of a renewable energy transition among the multiple other co-benefits that can be attributed to the numerical scenario. The results of the research work are expected to be beneficial in providing impetus for more sustainable coastal and coastal island cities despite the climate crisis. Perspectives for coastal settlements in Latin America, including Viña del Mar in Chile, are discussed among related opportunities in the world.